1999
DOI: 10.1021/jp984671j
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Oligomerization of Methane via Microwave Heating

Abstract: Catalytic microwave heating has been used as a method for the oligomerization of methane to higher hydrocarbons. Many catalysts were tested in this reaction. Nickel powder, iron powder, and activated carbon were the most active and efficient catalysts for the production of higher hydrocarbons. When helium was used as a diluent gas and the applied power was optimized, the selectivities were controlled to the most desired products. Iron powder was active only at high power (1130 W). At these conditions acetylene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 47 publications
2
31
1
4
Order By: Relevance
“…The results observed are in agreement with the results obtained by Marun et al [21], Suib and Zerger [22] and Suib [23]. In the oligomerization of methane to higher hydrocarbons carried out by Marun et al using microwave heating, their results showed arc formation and discharges produced by the catalyst.…”
Section: Reaction Of Methane Without Oxygen Under Microwave and Convesupporting
confidence: 91%
“…The results observed are in agreement with the results obtained by Marun et al [21], Suib and Zerger [22] and Suib [23]. In the oligomerization of methane to higher hydrocarbons carried out by Marun et al using microwave heating, their results showed arc formation and discharges produced by the catalyst.…”
Section: Reaction Of Methane Without Oxygen Under Microwave and Convesupporting
confidence: 91%
“…The results obtained are in line with that observed by other researchers [18][19][20][21]. In the study by Marun et al [18,19] on the oligomerization of methane to higher hydrocarbons using microwave heating, they observed both arc formation and discharges produced by the catalyst.…”
Section: Methane Conversionsupporting
confidence: 91%
“…In the study by Marun et al [18,19] on the oligomerization of methane to higher hydrocarbons using microwave heating, they observed both arc formation and discharges produced by the catalyst. Ethane was found to be the major product at the beginning of the reaction.…”
Section: Methane Conversionmentioning
confidence: 99%
“…AC and DC corona discharges, dielectric-barrier discharge, arc plasma, and the combination of microwave plasma and catalysts have been reported to produce acetylene, ethylene, hydrogen, methanol, and other liquid products (Wan, 1986;Mallinson et al, 1987;Bhatnagar and Mallinson, 1995;Liu et al, 1996;Thanyachotpaiboon et al, 1998;Onoe et al, 1997;Okumoto et al, 1998;Suib and Zerger, 1993;Marun et al, 1999;Eliasson et al, 2000;Yao et al, 2000d). Recently, methane reforming with CO, using plasmas, which may contribute to effective utilization of methane and reduction of greenhouse gas CO, emission, has been reported (Gesser et al, 1997;Bromberg et al, 1998;Larkin et al, 1998;Zhou et al, 1998;Huang et al, 2000;Yao et al, 2000b).…”
Section: Aiche Journal February 2001mentioning
confidence: 99%